Die Notwendigkeit der Einwohnerwertung - Horst Zimmermann (Wirtschaftsdienst, 2013)
In der Klage der Länder Bayern und Hessen vor dem Bundesverfassungsgericht gegen den Länderfinanzausgleich spielt die Einwohnergewichtung der Stadtstaaten eine große Rolle. Es lässt sich zeigen, dass diese gerechtfertigt ist, weil die Einwohner von Stadtstaaten - wenn sie dem kommunalen Finanzausgleich unterliegen würden - auch höher gewichtet würden als Einwohner von kleineren Städten ohne besondere Funktionen. Dabei sollte Berlin nicht als Sonderfall behandelt werden. Geht man von der Einwohnergewichtung ab oder sucht andere Lösungen für Berlin, so führt dies zu einer unerwünschten Asymmetrie im deutschen Föderalismus. – – German equalisation systems among states (Länder) and among communities assign higher expenditure needs to larger cities. For the system among the states (Länderfinanzausgleich), in which the three city-states are assigned a value of 135 compared to a value of 100 for the other states, this element is challenged in a pending case before the constitutional court. The paper argues that the city-states should be treated like any large city in Germany, which would result in their being assigned a value well above 135. The main justification for the higher value for larger cities is seen in the crucial role of modern agglomerations for national economic growth. To maintain this role, they have to be able to keep or receive enough public finances, given that they contribute to upper-level finances way above the average but receive relatively little through those levels' spending. The progressive scale smoothes at least some of this effect.
Keywords: H72; H73; H77; R51; 330